2017
DOI: 10.1016/s2214-109x(16)30308-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure deaths and their risk factors in India 2001–13: nationally representative estimates from the Million Death Study

Abstract: US National Institutes of Health, International Development Research Centre, Centre for Global Health Research, University of Toronto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…All co-authors contributed in an interactive process to the various sections of the drafts and approved the final version. Tazeen H Jafar, professor 8,9,10 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All co-authors contributed in an interactive process to the various sections of the drafts and approved the final version. Tazeen H Jafar, professor 8,9,10 …”
Section: Resultsmentioning
confidence: 99%
“…7 8 Stroke and chronic kidney disease may also occur earlier in South Asians. [9][10][11] The effect of lives lost due to premature cardiovascular disease is far worse in South Asia than elsewhere, as more than half of the population lives in conditions of poverty. 3…”
Section: Current Epidemiology and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a probable heavy burden of end-stage kidney disease in LMICs, relatively few patients receive renal replacement therapy. A 2015 systematic review suggests that approximately 83% of renal failure patients in Asia are not receiving the renal replacement treatment [22]. A recent Cochrane review which included 17 studies involving 1639 people with CKD showed that different modalities of dietary interventions were associated with improved kidney function and hemodynamic measures [23].…”
Section: Main Textmentioning
confidence: 99%
“…Reports from India, China, Sri Lanka and Algeria appeared indicating the correlation of fluoride excess consumption and renal failure44454647.…”
Section: Fluorosis and Linked Disordersmentioning
confidence: 99%